Formulasi dan Evaluasi Sifat Fisik Sediaan Masker Gel Peel Off Ekstrak Etanol Daun Afrika (Vernonia Amygdalina) - Budi Setiawan; Renatalia Fika; Tessa Levia Kasya (Program Studi DIII Farmasi Akademi Farmasi Dwi Farma, 2024)
African leaf (vernonia amygdalina) is a plant that has many benefits. The flavonoid content in it has been proven to help inhibit bacterial growth. African leaves that have been extracted thickly are formulated into a Peel off gel mask with a concentration of 6%. 3 Peel off gel mask preparation formulas, namely F1 (PVA 11%), F2 (PVA 13%), F3 (PVA 15%). The resulting masks were evaluated for physical properties including organoleptic tests, pH tests, spreadability tests, homogeneity tests, and drying time tests. The physical properties test of the peel off mask has met mask standards. The organoleptic test showed no signs of physical changes in the preparation after it was formulated into a mask. No fine grains were found in the homogeneity test of the preparation, in the spreadability test it still did not reach the standard due to the increase in base concentration in formulas 2 and 3. The average spreadability test result was 3.125 cm. For the test, the drying time for formulas 1, 2 and 3 was 24, 22, 21 minutes. These results have shown that the preparation meets the standards for drying preparations and is in accordance with the skin pH standard, namely 4.5-6.5.